Relationship between coronavirus anxiety, resilience, and attitudes toward complementary and alternative treatment among patients admitted to the COVID-19 Outpatient Clinic - Ahmet Karakoyun; Emel Bahadır Yılmaz; Arzu Yüksel (National Scientific Medical Center, 2024)
Aim: During the COVID-19 pandemic, the studies showed an increase in complementary and alternative therapy use. This study aimed to determine the relationship between coronavirus anxiety, resilience, and attitudes toward complementary and alternative treatment among patients admitted to the COVID-19 outpatient clinic. Material and methods: This is a descriptive and relational study. The sample consisted of 364 patients who applied to the pandemic outpatient clinic of a training and research hospital in Turkey. Data were collected using the Coronavirus Anxiety Scale, Brief Resilience Scale, and Scale for Attitudes toward Complementary and Alternative Medicine. The Mann-Whitney U test, the Kruskal-Wallis test, and the Spearman correlation test were used in data analysis. Results: There was a moderate and negative correlation (r = −0.332) between attitudes toward complementary and alternative medicine and coronavirus anxiety, and a moderate and positive correlation (r = 0.348) between attitudes toward complementary and alternative medicine and resilience (p < 0.01). Additionally, there was a moderate and negative correlation between coronavirus anxiety and resilience (r = −0.667; p < 0.01). Conclusion: In the COVID-19 pandemic process, it is essential to follow up on patients' complementary and alternative medicine use, inform them, and determine their causes.